DEVELOPMENT STRATEGY ELITE AND ELITE EDUCATION - N. L. Podvoiskaya (Современная наука и инновации, 2022)
The review concluded that the given monograph is a quite successful attempt to contribute to solving the problems of modern elitology education at a theoretical level. This was facilitated by the fact that the authors have long been working on this issue. The following features of this work are noted: a) an interdisciplinary nature, which necessitated several scientific measurements, and b) an emphasis on pedagogical selection of elites. As a positive aspect of the monograph it is emphasized that when considering almost all issues and problems the authors devoted a significant place to their historical aspects, current state, and prospects for their development. The authors expressed confidence that a close acquaintance with this monograph will contribute to understanding of the history, current status, problems, and prospects of Russian education in general, and elite I top-end education in particular by students, undergraduates and everyone who is interested in this issue.